(3bhi GdCOhjI GdeSgdI hWHGFYgG heRGLGJgG heUGdMgGs - (3jhMfG Hf eGShjg, CHh RcQjG,J (B243 (3g` s
(3ChdgG (B:s
(3aeG jdRe Cgd cd GdeYQaI hGdTQY GdcTa Yf GUhd GdMceI Cf jYdehG CdHGHge ai cd eG jQLY HGdaGFOI , hjUjQ Edi GdefGaY s
(3BNQgG (B:s
(3eHJhQ GdBNQ , hBNQ GdehLhO efg (B: (3CUd GdShS hNGUjJg ESgGd hjYUQ GdYfH , hdjcf eG jNJGQ efg eG cGf eSJWjdG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B60 - (3U(B67s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B263s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B185 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(255/1 (3c(B) s
Keywords: (3GdWHs